EFEKTIFITAS KORAN MASUK NAGARI (KMN) PADANG PARIAMAN HARIAN UMUM HALUAN DI KECAMATAN PARIAMAN SELATAN - Berlian, Mery (LPPM Universitas Terbuka, 2006)
This article defined some informations about the total ammount of Koran Masuk Nagari (KMN) Padang Pariaman where this news is very famous for local people. It also has many functions such as to measure a main message on the news, to measure the level of content messages in distribution, and identify some problems, which will be happened on distribution.The research were implemented in Kecamatan South Pariaman and used 57 house hold samples. Hence, I used qualitaitive method which has category in descriptive analysis. The most favourite information is about religion (21,44%), and the capability of understanding content of messages has got the lowest point (2). Because of KMN had not some special cars and staffs to distribute the news, therefore the distribution from publisher to people always be late and this is a classic problem for KMN to expand. The conclusion from this research showed that KMN Padang Pariaman was effective to improve the local people interest to read it. And the fact KMN is always be waited by people in Padang Pariaman.